مساهمة معايير المحاسبة الدولية في دعم الإفصاح المحاسبي - جودي, محمد رمزي; جودي, أمينة (Université de M'sila, 2017)
Companies seek to apply the international accounting standards which contribute to give more financial information to the users of the financial reports through the ccounting disclosure.This paper aims at defining the accounting disclosure, its sorts and its rincipals, plus defining the international accounting standards and its vantages,furthermore; identifying the accounting committees which issue these standards, hrough studying some international accounting standards and explaining the contribution of each standard in supporting the accounting disclosure. This study oncluded that the application of the international accounting standards contribute trongly in supporting the accounting disclosure, and meeting the needs of the financial reports users, through providing the financial information which cannot be provided in the raditional accounting systems. This fact calls for the need to impose the application of the accounting disclose in accordance with international accounting standards.
Keywords: Accounting Disclosure, International Accounting Standards.